Culture and crisis communication : transboundary cases from nonwestern perspectives - George, Amiso M.; Kwansah-Aidoo, Kwamena (IEEE PCS professional engineering communication series., 2017)
A collection of case studies from nonwestern countries that offers an analysis of the significant role culture plays in crisis communication Culture and Crisis Communication presents an examination of how politics, culture, religion, and other social issues affect crisis communication and management in nonwestern countries. From intense human tragedy to the follies of the rich, the chapters examine how companies, organizations, news outlets, health organizations, technical experts, politicians, and local communities communicate in crisis situations. Taking a wider view than a single country s perspective, the text contains a cross-cultural and cross-country approach. In addition, the case studies offer valuable lessons that organizations that wish to operate or are operating in those cultures can adopt in preparing and managing crises. The book highlights recent crisis events such as Syria s civil war, missing Malaysia Flight MH370, andJapan s Fukushima Daiichi nuclear power plant disaster. Each of the case studies examines how culture impacts communication and responses to crises. Authoritative, insightful, and instructive, this important resource: Analyzes how nonwestern cultures respond to crises Covers therole of culture in crisis communication in recent news events Includes contributions from 18 international authors who provide insight on nonwestern culture and crisis communication Written for communication professionals, academics, and students, Culture and Crisis Communication presents an insightful introduction to the topic of culture and crisis communication and then delves into illustrative case studies that explore intra-cultural and trans-boundary crisis communication.